Formulasi Tablet Salut Selaput Katekin dari Ekstrak Gambir (Uncaria gambir Roxb.) - Kurniatri, Arifayu Addiena; Adelina, Rosa; Setyorini, Herni Asih; Sulistyowati, Indah (Jurnal Kefarmasian Indonesia, 2015)
Gambir extract contains a high content of catechin. Catechin has so many benefits, such as antioxidant, antimicrobial, and anti-atherosclerosis.Gambir are widely available in Indonesia, especially in West Sumatra, might be a sustainable source of catechin. Catechin is easily oxidized and hygroscopic. Film coating is used to protect catechin contained in a tablet from moisture and light. Study of film-coated tablet of catechin has not been conducted before. This study aims to formulate film-coated tablet of catechin from gambir and evaluate its physical properties. Catechin was percolated from gambir extract using ethyl astetat. The ethyl acetate fraction of gambir extract contains 92,48±0,28% catechin. Tablets were compressed with direct compression method and coated with a polymer coating material. The physical properties of core tablet and film-coated tablet were evaluated toward weight uniformity, hardness, friability, and disintegration time. Friability testing was conducted only on core tablet. The formulation produced tablets with uniform weight, 16,6 ±1,97 Kp hardness, and 4 minutes 15 seconds disintegration time. Weight uniformity and disintegration time of the tablet meet the requirements.